Development of Animated Learning Video Media Based on Problem Based Learning (PBL) Model on Human Skeleton Material to Improve the Learning Outcomes of Sixth Grade Students at SDN Liprak Kidul I - Vira Amilia Nur; Didit Yulian Kasdriyanto; Faridahtul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to improve the learning outcomes of sixth-grade students at SDN Liprak Kidul I through the development of Problem Based Learning (PBL)-based instructional video media on the human skeletal system. The research was motivated by several learning problems, including low student achievement, limited availability of attractive teaching materials, monotonous learning activities, and the lack of interactive media that could encourage active student participation. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research procedures included needs analysis, product design, media development, expert validation, product revision, product trials, and evaluation. The subjects of this study were sixth-grade students at SDN Liprak Kidul I. The instruments used included media and material expert validation sheets, teacher and student response questionnaires, and student learning outcome tests. The results showed that the developed instructional video media had a high level of validity, practicality, and effectiveness. Media expert validation obtained a score of 94%, while material expert validation reached 95%, indicating that the media was highly feasible for use in learning. Teacher and student responses also showed very positive results, with scores of 93.75% and 95.45%, respectively. The use of PBL-based instructional video media increased students’ attention, engagement, and motivation during the learning process. In addition, the media effectively improved students’ understanding and learning outcomes related to the human skeletal system. Therefore, this media is considered feasible, practical, and effective for IPAS learning in elementary schools.